Pelatihan Manajemen Referensi Menggunakan Mendeley untuk Menulis Artikel Ilmiah bagi Guru-guru MGMP SMP Negeri di Pekanbaru - Asnawi Asnawi; Sri Wahyuni; Alber Alber; Fauzul Etfita (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2021)
Writing scientific articles is closely related to the references used. The arrangement of references in a scientific article indicates that the article is written based on relevant sources. The current problem faced by teachers in writing scientific articles is the inability to manage references using Mendeley. Therefore, it is necessary to conduct reference management training using Mendeley in writing scientific articles. This activity aims to make it easier for teachers to do citations from various existing reference sources. The activity was carried out for MGMP SMP Negeri Pekanbaru. Participants in this training amounted to 25 teachers spread throughout the city of Pekanbaru. The training method used is in the form of guided guidance. Based on the results and discussion of the activities carried out, it can be concluded that the reference management training using the Mendeley application to write scientific articles for MGMP SMP Negeri Pekanbaru is very effective. The effectiveness of this activity is due to an increase in intelligence in more specific aspects, such as increasing participants' understanding and skills in managing references using the Mendeley application. With Mendeley, teachers can streamline and document several reference sources easily. In addition, Mendeley is also very helpful for teachers in writing scientific articles to be published in the Open Journal System (OJS). Overall, it can be stated that this activity plays an important role for teachers because it can effectively improve the professional competence of teachers in facing future challenges.